Career Transition to Non-Tenure-Line Faculty: Midlife Women’s Challenges, Supports, and Strategies - Catherine A Cherrstrom (Adult Education Research Conference, 2017)
Numbers of new faculty with prior careers, women faculty, and non-tenure-line faculty are increasing. This study investigated the career transitions and strategies of women midlife career changers to non-tenure-line faculty.
Keywords: career transition; career change; midlife; faculty; higher education